Climbing the ladders of job satisfaction and employee organizational commitment: Cross-country evidence using a semi-nonparametric approach - José António Cabral Vieira; Francisco José Ferreira Silva; Jo\~ao C. A. Teixeira; António J. V. F. G. Menezes; Sancha N. B. de Azevedo (Journal of Applied Economics, 2023)
Satisfied and committed employees play a major positive role in business performance in today's globalized and competitive landscape. This paper contributes to the literature on the empirical determinants of job satisfaction and organizational commitment, drawing on a rich micro dataset for 36 countries, using a flexible semi-nonparametric approach, which nests and outperforms the standard ordered probit model. The findings indicate that job satisfaction and organizational commitment can be fostered by instruments which can be controlled by management. Our results shed timely light on how managers can improve job satisfaction and organizational commitment and address implications of the Great Resignation. However, despite the ever-increasing pace of globalization and expanding role of multinationals across the globe in shaping work environments, our results uncover that significant cross-country differences in job satisfaction and organizational commitment do exist, even after controlling for a plethora of job-and-workplace manageable attributes and individual (including religious dimensions) related characteristics.
Keywords: 330; cross-country differences; employee organizational commitment; great resignation; Job satisfaction